Eigenvalues of non linear problems lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Varenna (Como), Italy, June 16-25, 1974 - Prodi, G. 1925- (Giovanni) (CIME summer schools, 2010)
H. Amann: Nonlinear eigenvalue problems in ordered Banach spaces.- P.C. Fife: Branching phenomena in fluid dynamics and chemical reaction-diffusion theory.- W. Klingenberg: The theory of closed geodesics.- P. Rabinowitz: Variational methods for nonlinear eigenvalue problems.- M. Reeken: Existence of solutions to the Hartree-Fock equations.- R. Turner: Positive solutions of nonlinear eigenvalue problems.